Entrepreneur motivation to start business / Amirul Hakim Mohamad and Nur Fadhila Aziz - Mohamad, Amirul Hakim; Aziz, Nur Fadhila (Faculty of Business and Management, 2014)
Entrepreneurship is one of the activities that Johor government encourages people to create business. There are many successful entrepreneurs in Johor brings a very proud products and services. The purpose of this research also is to identify the relationship between entrepreneur motivation to start business and the independent factors such as internal motivation, government support, capabilities, and financial security. Besides that it also to identify which factors is the most significant factor for entrepreneur motivation to start business towards the internal motivation, government support, capabilities and financial security. Hence, this research used primary and secondary data in collection the data as data method. As for the interpretation data, the researcher used correlation coefficient for testing hypothesis, while regression analysis for testing the most significant variables in this research. Based on the researcher findings, the factor of internal motivation, government support and capabilities overall have positive correlation with the entrepreneur motivation to start business while the financial security shows the negative relationship with entrepreneur motivation to start business. In addition, only the government support and capabilities are not at the level of significant where as the internal motivation and financial securities are in significant. Thus, the most significant variable is financial security shows the most factors influencing entrepreneur motivation to start business.